Integrasi Mikroskala dan Green Chemistry terhadap Keterampilan Proses Sains - Putriani; Eda Lolo Allo; Dewiyanti Fadly (PEDAGOGIKA, 2026)
This study aims to examine the role of microscale and green chemistry approaches in supporting students’ science process skills (SPS) through a Systematic Literature Review (SLR) using the PRISMA protocol. Data were collected from Scopus, ERIC, and Google Scholar within the 2016–2026 publication range, resulting in 25 selected articles after a four-stage screening process. The findings indicate that microscale approaches consistently support improvements in conceptual understanding, student engagement, and the quality of experimental activities by using smaller quantities of chemicals and safer procedures. The integration of green chemistry principles not only enhances environmental awareness but also encourages more responsible learning practices. In addition, the use of simple technologies, such as smartphones, contributes to more accurate observation and data analysis. Overall, the integration of microscale and green chemistry demonstrates strong potential in supporting science process skills and remains highly relevant for sustainable and 21st-century chemistry learning.